Pelatihan Kepemimpinan dan Kewirausahaan bagi Masyarakat dan Perangkat Desa Waisala Kecamatan Huamual Kabupaten Seram Bagian Barat - Louhenapessy, William George Mozes; Salong, Amjad; Ubra, Franklin William (Universitas Pattimura, 2024)
This study analyzes the impact of a leadership and entrepreneurship training program in Waisala Village, highlighting its positive effects on participants, the community, and the environment. The impact evaluation showed an increase in participants' knowledge and skills, as well as active participation in community economic and social activities. Supporting factors, such as a participatory approach and the quality of facilitators, supported the success of the program, although resource constraints and participant expectation management were barriers. The implications of this study's results reinforce the need to involve participants in program development, improve the quality of facilitators, and address resource constraints to support program sustainability. By taking these steps, the leadership and entrepreneurship training program can continue to provide positive and sustainable impacts for participants, the community, and the environment, and become a model for the development of similar programs in the future.